The Review of Automotive Industry in Malaysia: Good Governance Perspective - Manimaharan, Malini; Suhaidah, Hussain; Muhammad Ashraf, Fauzi (Science Research Society, 2021)
The automotive sector has a key role in domestic growth and contributes to governance. The manufacturing sector contributes to the growth and prosperity of the country. Industry manufacturing creates well-paid jobs, encourages technological development and raises sales. Production is one of the world's most dynamic industries. In order to assure process continuity and repeatability, good governance is adopted in the manufacturing industry. The evaluation stated that effective management practices must be cascaded to the lowest level from the highest level in the business. Governance initiatives allow the organization to perform more efficiently and efficiently. Good governance provides valuable goods, which produces wonderful market results. Good governance gives the organization and a safe community a positive image.